2012
DOI: 10.3329/jbau.v9i2.11038
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of evapotranspiration using a simulation model

Abstract: Practical methods for the accurate estimation of water requirement for irrigated agriculture are essential. Simulation model is a useful tool to estimate water balance in the crop field. In this study, the BUDGET model was used to evaluate its performance to simulate water balance in wheat field. The BUDGET model is composed of a set of validated subroutines describing the various processes involved in water extraction by plant roots and soil water movement in absence of a water table

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Irrigation scheduling determines the agronomic and economic benefits of farms. Hence, irrigation scheduling is important for developing best management practices for irrigated areas (Ali et al, 2011). The irrigation water is applied to the cultivation according to predetermined schedules based upon the monitoring of the soil water status and the crop water requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation scheduling determines the agronomic and economic benefits of farms. Hence, irrigation scheduling is important for developing best management practices for irrigated areas (Ali et al, 2011). The irrigation water is applied to the cultivation according to predetermined schedules based upon the monitoring of the soil water status and the crop water requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Ethiopia is a country, with land coverage of 1.13 Million km 2 , found in Eastern part of Africa [3]. The country is geographically located in between the latitudes 5°N and 15°N, and longitudes 35°E and 45°E [15].…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation is defined as the application of suitable water to crops in appropriate amount at the right time [8]. Irrigation scheduling is required for developing best irrigation water management practices for irrigated areas [2].…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation implies the application of suitable water to crops in the right amount at the right time [11] Irrigation scheduling is important for developing best management practices for irrigated areas [5]. There is considerable scope for improving water use efficiency of these crops by proper irrigation scheduling governed by crop evapotranspiration [12,5] have suggested that the crop coefficient values need to be derived empirically for each crop based on lysimetric data and local climatic conditions.…”
Section: Introductionmentioning
confidence: 99%